DISCIPLINES IN THE SPECIALTY AS A MEANS OF DEVELOPING THE PROFESSIONAL COMPETENCE OF FUTURE TEACHERS OF THE RUSSIAN LANGUAGE - Kozlova , Lola Salimbekovna (Educational Research in Universal Sciences, 2023)
The article provides information on the development of professional competence of future teachers of the Russian language in the class for the study of disciplines in the specialty, at all stages of education in a higher educational institution, and also analyzes the compliance of the content of the training module with the requirements of the State Educational Standard of the Republic of Uzbekistan.